2007
DOI: 10.1177/1077801206296980
|View full text |Cite
|
Sign up to set email alerts
|

Latinos’ Perspectives and Experiences With Intimate Partner Violence

Abstract: This qualitative study, utilizing focus group interviews with community members and in-depth interviews with victims and perpetrators, explored Latinos' beliefs and perceptions of IPV in Oklahoma City, Oklahoma, as a basis for developing culturally appropriate intimate partner violence (IPV) services for this population. The findings from these interviews suggest that this community recognizes IPV as a problem and is aware of the multiple dimensions, potential causes, and negative consequences of IPV. In gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 18 publications
3
59
1
3
Order By: Relevance
“…According to Klevens et al (2007), B…individuals cannot be separated from their cultural context…^and thus we must understand differences observed between ethnic or cultural groups. In 2007, Klevens conducted a review of existing research on IPVamongst Hispanics.…”
Section: Culture and Help-seekingmentioning
confidence: 99%
“…According to Klevens et al (2007), B…individuals cannot be separated from their cultural context…^and thus we must understand differences observed between ethnic or cultural groups. In 2007, Klevens conducted a review of existing research on IPVamongst Hispanics.…”
Section: Culture and Help-seekingmentioning
confidence: 99%
“…Many studies have identified that responses received from family and friends are not always helpful (Clark et al, 2010;Fanslow & Robinson, 2010;Goodkind et al, 2003;Klevens et al, 2007, Lempert, 1997, indicating a considerable potential for change. This is reinforced by our finding that 70% of our participants had experienced interactions with families and/or friends that they found negative or unhelpful.…”
Section: Women and Supportmentioning
confidence: 99%
“…The number of different factors at play for any particular woman means that simple, clear cut, differences by characteristics such as ethnicity or culture are not found in the literature (Jones, Bogat, Davidson, Von Eye, & Levendosky, 2005;Savage & Russell, 2005). Responses received from family and friends are not always helpful (Clark, Silverman, Shahrouri, Everson-Rose, & Groce, 2010;Fanslow and Robinson, 2010;Goodkind, Gillum, Bybee, & Sullivan, 2003;Klevens et al, 2007, Lempert, 1997, and fear of possible negative or unhelpful reaction is one factor that can make women reluctant to talk to families and friends about their experiences. In some cases there is also direct involvement of family members, particularly in-laws, in the abuse experienced (Clark et al, 2010;Gangoli & Rew, 2011;García-Moreno et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Emotional abuse occurs when a person verbally attacks another person with disrespect or fury (e.g., criticism of others' appearance or personality, mockery, teasing, and swearing) that may generate psychological pain. [4] Emotional abuse carries with it negative social, physical, and emotional consequences such as depression, hostility, and somatization [4] in addition to detrimental effects on women's gynecological, gastrointestinal, and central nervous systems.…”
Section: Introductionmentioning
confidence: 99%